2017
DOI: 10.3390/nu9090971
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein and Amino Acid Profiles in Relation to Risk of Dysglycemia: Findings from a Prospective Population-Based Study

Abstract: Considering the limited knowledge on the effects of dietary amino acid intake on dysglycemia, we assessed the possible association of dietary protein and amino acid patterns with the risk of pre-diabetes in a prospective population-based study. Participants without diabetes and pre-diabetes (n = 1878) were recruited from the Tehran Lipid and Glucose Study and were followed for a mean of 5.8 years. Their dietary protein and amino acid intakes were assessed at baseline (2006–2008); demographic, lifestyle, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
5
6
0
1
Order By: Relevance
“…Thus, not a high protein intake in general but the protein quality may play a crucial role for modulating disease risk [ 16 , 17 ]. This is in line with other studies showing that not the total protein intake itself but the protein composition or the AA pattern is important with regard to risk of T2D and CVD [ 37 , 38 , 39 ]. These results strengthen our hypothesis that the dietary pattern beyond the intake of BCAA rather than the effect of BCAA intake itself contribute to the increased risk for chronic diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, not a high protein intake in general but the protein quality may play a crucial role for modulating disease risk [ 16 , 17 ]. This is in line with other studies showing that not the total protein intake itself but the protein composition or the AA pattern is important with regard to risk of T2D and CVD [ 37 , 38 , 39 ]. These results strengthen our hypothesis that the dietary pattern beyond the intake of BCAA rather than the effect of BCAA intake itself contribute to the increased risk for chronic diseases.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, using two prospective cohorts, a positive association between the AACI and incidence of (33), and they are also supported by cell and animal studies with the fact that feeding with mixture of AAs rather than a single AA alone could promote development of insulin-resistance and β-cell dysfunction in rodents (34,35). Taken together, these accumulating evidences suggest that dietary AAs composition is likely an important risk factor in prevention and management of T2DM.…”
Section: Discussionsupporting
confidence: 80%
“…This study also demonstrated that when additionally adjusted for other known dietary risk factors for T2DM including intake of total protein (29), ber (30), saturated fat (31), and overall diet quality (32), the relationship between the AACI and incidence of T2DM was still signi cant, further indicating that inadequate dietary AAs composition was likely an important dietary factor for residual risk of T2DM. These ndings are supported by previous study showing that risk of pre-diabetes varied with different dietary AAs patterns (33), and they are also supported by cell and animal studies with the fact that feeding with mixture of AAs rather than a single AA alone could promote development of insulin-resistance and β-cell dysfunction in rodents (34,35). Taken together, these accumulating evidences suggest that dietary AAs composition is likely an important risk factor in prevention and management of T2DM.…”
Section: Discussionsupporting
confidence: 79%